O ÊXODO COMO TRADIÇÃO FUNDANTE DE ISRAEL NORTE A PARTIR DE 1REIS 12,26-32 - TOSELI, CECILIA (2016)
This paper presents the Exodus-Desert tradition as Northern Israel foundational tradition, consolidated in the 8th century BCE, based on Bible reading 1 Kings 12.26 to 32. The passage 1 Kings 12.26-32 presents Jeroboam's religious measures to consolidate the independence of the newly founded Northern Kingdom, in relation to the "house of David" and the "house of Yahweh in Jerusalem" (v. 26-27). The passage perspective is clearly Judahite. However, we believe that, behind the 1 Kings 12.26-32 narrative, there are Exodus echoes as Northern Israel foundational tradition, consolidated during Jeroboam II reign (788-747). We have placed the historical core of the Exodus cultural memory in Northern Israel into the context of Sheshonq I military campaign (945-925) in Canaan, in the second half of the 10th century BCE. Although the "house of Saul" political-territorial defeat, located on the Gibeon-Bethel Plateau, the forced withdrawal of Egypt (for unknown reasons), in a short time, reignited the victory and freedom feeling in the remaining groups of the mountains, after centuries of Egyptian domination in Canaan. Therefore, the Exodus is born as a memory of fight against Egypt, and not as migration from Egypt. Thus, the Exodus God is conceived as a warrior divinity who leads his people, ensuring them victory. The Egypt withdrawal from Canaan lands shaped the path for Israel kingdom consolidation, under the Omrides govern, in the beginning of the 9th century BCE. Thus, it is possible to understand that the memory of freedom from Egypt has become an emblematic propaganda of the national state victory against his great enemy, after centuries of suffering and humiliation. On the other hand, the Exodus tradition remains as the resistance force against monarchical exploitation and oppression, as evidenced by Hosea and Amos' prophecy, in the 8th century BCE. The Desert tradition was an independent memory. It was attached to the Exodus tradition, probably during Jeroboam II reign (788-747), as evidenced by inscriptions and drawings located at Kuntillet 'Ajrud site. Based on Hosea and Amos' prophecy and according to Kuntillet 'Ajrud records, we consider that the national cult in Northern Israel, in the 8th century BCE, was dedicated to the Yahweh, represented as the "young bull" and associated with the Exodus, in shrines as Bethel, Dan, and Samaria. However, before Yahweh became Israel tutelary divinity, Egypt liberation memory had been assigned initially to the god El, an Ugarit pantheon supreme divinity, traditionally represented as a bull and associated with Asherah goddess. Another Northern Israel foundational narrative competes with the Exodus tradition during Jeroboam II reign, the Jacob tradition, associated with family memories. However, after Samaria fall, Jacob's old memories are once again read in Judah, submitted to Abraham tradition and supplanted by the Exodus tradition, which then becomes, from the end of the 7th century BCE, the foundational narrative of a unified Israel, considered one people from the beginning.